Testing the causal impact of plasma amyloid on total Tau using a genetically informative sample of adult male twins - Nathan A. Gillespie; Michael C. Neale; Matthew S. Panizzon; Ruth E. McKenzie; Xin M. Tu; Hong Xian; Chandra A. Reynolds; Michael J. Lyons; Robert A. Rissman; Jeremy A. Elman; Carol Franz; William S. Kremen (Aging Brain)
The amyloid cascade hypothesis predicts that amyloid-beta (Aβ) aggregation drives tau tangle accumulation. We tested competing causal and non-causal hypotheses regarding the direction of causation between Aβ40 and Aβ42 and total Tau (t-Tau) plasma biomarkers. Plasma Aβ40, Aβ42, t-Tau, and neurofilament light chain (NFL) were measured in 1,035 men (mean = 67.0 years) using Simoa immunoassays. Genetically informative twin modeling tested the direction of causation between Aβs and t-Tau. No clear evidence that Aβ40 or Aβ42 directly causes t-Tau was observed. Instead, the alternative causal hypotheses also fit the data well. In contrast, exploratory analyses suggested a causal impact of the Aβ biomarkers on NFL. Separately, reciprocal causation was observed between t-Tau and NFL. Plasma Aβ40 or Aβ42 do not appear to have a direct causal impact on t-Tau, though our use of total rather than phosphorylated tau was a limitation. In contrast, Aβ biomarkers appeared to causally impact NFL in cognitively unimpaired men in their late 60 s.